Kangerdlugssuaq Glacier surface flow speeds from feature tracking, 1985-2018 - Bevan, Suzanne; Luckman, Adrian (UK Polar Data Centre, Natural Environment Research Council, UK Research & Innovation, 2019)
Surface speeds for a point close to the front of Kangerdlugssuaq Glacier based on satellite image feature tracking from 1985 to 2018. : Feature tracking of satellite images of Kangerdlugssuaq Glacier was used to measure surface velocities between April 1985 and November 2018. The satellite images include Landsat 5, Landsat 7, Landsat 8, ERS-1, ERS-2, Envisat Image Mode, TerraSAR-X and Sentinel 1A and B Single Look Complex images. The dataset has been compiled over approximately 20 years and processing algorithms and parameters have evolved and improved. The more recent measurements are likely to be the most accurate. : Image processing and feature tracking were carried out using Gamma Remote Sensing software. : The accuracy of the data varies according to the initial spatial resolution and geolocation of the images and is likely to improve throughout the time sequence as processing and algorithms have improved. Bevan et al. (2012) estimated the accuracy of all types of images up to 2012 to be better than 0.5 metres/day.